Galectin-3 is inversely associated with cardiorespiratory fitness in the general population. (11th May 2021) - Haid, M; Bahls, M; Doerr, M; Felix, S; Zylla, S; Markus, M; Friedrich, N; Ewert, R; Glaeser, S
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Low cardiorespiratory fitness (CRF) is associated with high mortality and morbidity. Galectin-3 (Gal-3) is a prognostic biomarker for fibrosis, different cancers, renal impairment and, in particular, for heart failure. Further, higher Gal-3 levels are associated with increased cardiovascular mortality. Whether Gal-3 is related with the protective effects of a high CRF is unclear. Purpose: The present study examined the relation between Gal-3 and CRF as determined by body weight adjusted peak oxygen uptake (VO2peak/kg), oxygen uptake at the anaerobic threshold (VO2@AT) and maximal workload (Wmax). Methods: We used data of the population-based Study of Health in Pomerania (SHIP-TREND) from Northeast Germany. A total of n = 1, 483 participants with a median age of 49 (IQR: 39 – 59 years, male 48%) were included in the analysis. CRF parameters were measured using standardized cardiopulmonary exercise testing on a bicycle ergometer. Plasma galectin‐3 concentrations were determined using a quantitative sandwich enzyme immunoassay. Individuals with left ventricular ejection fraction < 40%, previous myocardial infarction, atrial fibrillation, chronic lung disease, severe renal disease (eGFR < 30 ml/min/mm2), a history of cancer, and extreme values for Gal-3 were excluded. Linear regression models adjusted for age, sex and lean mass were used to analyze the association between Gal-3 and CRF. Results: A one ml/min/kg greater VO2peak was related to a 0.32 ng/ml (95% confidence interval [CI] -0.45 to -0.18, p <.001) lower Gal-3. Further, a one Watt larger power output was also associated with a 1.32 ng/ml (95% CI -2.10 to – 0.54, p <.001) lesser Gal-3. VO2@AT was not related to Gal-3 (β: -3.31 95% CI -8.68 to 2.05, p = .23). Conclusions: In the general population Gal-3 is inversely associated with CRF. Further studies should investigate whether lower Gal-3, beyond its importance as a biomarker for heart disease, may even play a role in the protective effect of the CRF.